2018
DOI: 10.1016/j.amsu.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of laparoscopic cholecystectomy (LC) related major bile duct injuries; predictors of short-and long-term outcomes in a tertiary Egyptian center- a retrospective cohort study

Abstract: ObjectivesLaparoscopic cholecystectomy - associated bile duct injury is a clinical problem with bad outcome. The study aimed to analyze the outcome of surgical management of these injuries.Patients and methodsWe retrospectively analyzed 69 patients underwent surgical management of laparoscopic cholecystectomy related major bile duct injuries in the period from the beginning of 2013 to the beginning of 2018.ResultsRegarding injury type; the Leaking, Obstructing, leaking + obstructing, leaking + vascular, and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 89 publications
(219 reference statements)
2
18
0
4
Order By: Relevance
“…Our cohort study included 410 patients with the following inclusion criteria: infants with a sure diagnosis of BA, Type III BA, completed KPE and operation done at our Institute, however, the exclusion criteria were cases that did not complete the follow-up, cases with data loss and cases of research refusal. It is a single institutional retrospective analysis of a prospectively collected database that analyzed the short- and long-term outcomes after this operation in the period from the beginning of 2000 to mid-2020 after approval of our institutional review board (IRB); where patients were observed from POD1 until the end of June 2020 or until the death of patients with a median follow up period of 44 (range, 0.2–243) months [ 29 , 30 ]. The study was registered in the Chinese clinical trial registry with registration NO of ChiCTR2000038541(Web site: Chinese Clinical Trial Registry (ChiCTR))…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our cohort study included 410 patients with the following inclusion criteria: infants with a sure diagnosis of BA, Type III BA, completed KPE and operation done at our Institute, however, the exclusion criteria were cases that did not complete the follow-up, cases with data loss and cases of research refusal. It is a single institutional retrospective analysis of a prospectively collected database that analyzed the short- and long-term outcomes after this operation in the period from the beginning of 2000 to mid-2020 after approval of our institutional review board (IRB); where patients were observed from POD1 until the end of June 2020 or until the death of patients with a median follow up period of 44 (range, 0.2–243) months [ 29 , 30 ]. The study was registered in the Chinese clinical trial registry with registration NO of ChiCTR2000038541(Web site: Chinese Clinical Trial Registry (ChiCTR))…”
Section: Introductionmentioning
confidence: 99%
“…Univariate analysis and then multivariate analysis (by Binary logistic regression method or Cox regression method) were done to detect the relationship between the different pre-, intra-, and post-operative variables and jaundice clearance at the 6th-month post-operatively as well as the relation between these variables and long-term(20-year) NLS. The Kaplan–Meier method was used for survival analysis to assess the long-term NLS and its predictors as well as the overall survival, a P-value of <0.05 was significant [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the conclusion of the registry is that cholecystectomy should not be delayed in patients with an adequate indication. One of the largest series of laparoscopic cholecystectomies in cirrhotic patients was recently published by Gad et al [23]. In a cohort of 213 cirrhotic patients operated between 2011 and 2019, 30-day morbidity and mortality were 22.1 and 2.3%.…”
Section: Cirrhosismentioning
confidence: 99%
“…20 Controversies about the treatment of these patients continue, however, the control of sepsis, biliary peritonitis, and timely referral to patients, a multidisciplinary approach in a center with experience in this type of case, can improve the results and improve morbidity and survival and is an essential and recommended step when making decisions in this type of patients. 21,22 Bile duct injuries remain severe complications of biliary tract surgery. Different factors affect their outcomes.…”
Section: 10mentioning
confidence: 99%